Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/annrheumdis-2021-eular.5012
|View full text |Cite
|
Sign up to set email alerts
|

Lb0001 mavrilimumab Improves Outcomes in Phase 2 Trial in Non-Mechanically-Ventilated Patients With Severe Covid-19 Pneumonia and Systemic Hyperinflammation

Abstract: Background:Granulocyte/macrophage-colony stimulating factor (GM-CSF) is a cytokine both vital to lung homeostasis and important in regulating inflammation and autoimmunity1,2,3 that has been implicated in the pathogenesis of respiratory failure and death in patients with severe COVID-19 pneumonia and systemic hyperinflammation.4-6 Mavrilimumab is a human anti GM-CSF receptor α monoclonal antibody capable of blocking GM-CSF signaling and downregulating the inflammatory process.Objectives:To evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…However, clinical anti-GM-CSF therapy has generated mixed results in various COVID-19 trials. The anti-GM-CSFRα mavrilimumab demonstrated efficacy in a Phase 2 trial [32]; however, the Phase 3 trial did not meet the primary endpoint, leading to its discontinuation in COVID-19 [33]. Anti-GM-CSF namilumab demonstrated a reduction in CRP in the CATALYST trial and trends toward clinical improvement, but the study was not powered for these outcomes [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical anti-GM-CSF therapy has generated mixed results in various COVID-19 trials. The anti-GM-CSFRα mavrilimumab demonstrated efficacy in a Phase 2 trial [32]; however, the Phase 3 trial did not meet the primary endpoint, leading to its discontinuation in COVID-19 [33]. Anti-GM-CSF namilumab demonstrated a reduction in CRP in the CATALYST trial and trends toward clinical improvement, but the study was not powered for these outcomes [34].…”
Section: Discussionmentioning
confidence: 99%
“…OSCAR had similarly broad lung injury-based entry criteria as BREATHE, including patients on high-flow oxygen (⩾15 L/min) as well as mechanical ventilation, and also required CRP or ferritin to be above the upper limit of normal. The phase 2 portion of a phase 2/3 randomized controlled trial of anti–GM-CSFR mavrilimumab demonstrated improvement in ventilator-free survival versus placebo in the cohort of hospitalized nonventilated patients ( N = 116) ( 35 ). A proof-of-concept phase 2 trial of anti–GM-CSF namilumab and anti-tumor necrosis factor–α infliximab in patients with COVID-19 pneumonia and CRP ⩾40 mg/L demonstrated a significant reduction in CRP concentration with namilumab, but not infliximab, relative to standard of care ( N = 146) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remdesivir is the only antiviral agent which has been granted full approved by the US FDA for the treatment of severe hospitalized patients with SARS-CoV-2. 55 Whereas, molnupiravir has been granted an EUA for the treatment of severe Covid-19 in hospitalized patients. 56 Both biologics can be used to treat nonhospitalized patients with mildto-moderate SARS-CoV-2.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…58,59 The standard of care (SoC) include high-flow nasal oxygen (HFNO), corticosteroids, remdesivir, and interlekin-6 antagonists, such as tocilizumab, or a Janus kinase inhibitor, including baricitinib. [48][49][50][51][52][53][54][55][56][57][58][59] Critically ill patients with Covid-19 require admission to the intensive care units (ICU), invasive mechanical ventilation (IMV) or extracorporeal membrane oxygenation (ECMO). However, ICU admission, and IMV or ECMO are associated with high hospital costs, prolonged multisystem disabilities, such as neurological impairment.…”
Section: Treatmementmentioning
confidence: 99%